Formulation Of A Maximum Power Point Tracking (Mppt) Algorithm For Hydrokinetic Energy Harnessing - Muhammad Naqib, Mazalan (2022)
This thesis is about a performance analysis based on Maximum Power Point Tracking (MPPT) algorithm generated by the hydrokinetic energy. The goal in this research is to formulate Modified Hill-Climbing Search algorithm with combination of PI controller to get the most power out of the system while lowering the oscillations. The experiment was conducted by using Permanent Magnet Synchronous Generator (PMSG), a threephase bridge rectifier, and a DC boost converter. The MPPT idea relies on detecting the rectifier output voltage and current to produce reference current (IMPP). The PIcontroller was employed to modify the error signal between IMPP and actual inductance current (Idc) to provide the duty-cycle for boost converter. The results will be evaluated based on energy harnessing and performance efficiency between HCS and proposed algorithm. The results demonstrate that the proposed method has 558.7W with 87.78% of efficiency in harnessing the power.